Virus elimination – a key for potential garlic production - Jayaswall, Kuldip; Benke, Ashwini; Gawande, Suresh; Bomble, Ram; Shelke, Poonam; Ghodke, Pranjali; Singh, Major (Indian Horticulture, 2019)
Garlic being non-flowering and clonally propagated species, geneticimprovement through breeding techniques is not applicable. Further forgetting higher production non-availability of disease-free quality plantingmaterial is a big hurdle. Besides, soil-borne diseases, virus infection playsa crucial role not only in reducing yield but degenerate quality and potentialof planting material. Therefore, availability of user-friendly virus eliminationtechnique will be a breakthrough in production and generation of virusfreegarlic planting material.